Modelling of hydraulic turbine for dynamic studies and performance analysis - Yin Chin Choo; Muttaqi, K.M.; Negnevitsky, M. (2007 Australasian universities power engineering : Perth, Australia : 9-12 December 2007, 2007)
Classical ideal lossless representation of the hydraulic turbine has been used widely in the past for governor stability studies. This model is suitable for small perturbations around the initial operating condition, and approximates to the practical turbine characteristics at low frequencies only. For satisfactory fast response and stable operation of governor studies, this classical model may not be adequate, rather a more accurate modelling of the turbine-penstock characteristics is desired to capture and depict the essential dynamic performances for wide variety of system analyses. In this paper, a hydraulic turbine model with long penstock is represented where the water hammer effects and friction are taken in consideration. A detailed hydraulic turbine-penstock utilised for governing stability studies is used to analyse the transient response when subject to a load disturbance. Frequency response analysis as well as transient response analysis is performed to evaluate the effects of the detailed modelling of the turbine-penstock to the stability analyses and the dynamic performances.